Impact of Financial Incentives on Employee Commitment in Nepalese Commercial Banks - Sundas, Muna (Nepalese Journal of Finance, 2024)
This study examines the impact of financial incentives on employee commitment in Nepalese commercial banks. Employee commitment is the dependent variable. The selected independent variables are bonus, compensation, pay, incentives, and recognition. The primary source of data is used to assess the opinions of respondents regarding bonus, compensation, pay, incentives, and recognition. The study is based on primary data of 129 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of financial incentives on employee commitment in Nepalese commercial banks. The study showed a positive impact of bonus on employee commitment. It indicates that higher the bonus, higher would be the employee commitment. Similarly, the study showed a positive impact of compensation on employee commitment. It indicates that higher the compensation, higher would be the employee commitment. The study also revealed a positive impact of pay on employee commitment. It indicates that higher the pay, higher would be the employee commitment. Likewise, the study observed a positive impact of incentives on employee commitment. It indicates that higher the incentives, higher would be the employee commitment. Similarly, the study observed a positive impact of recognition on employee commitment. It indicates that recognition of employee leads to increase in employee commitment.